2010
DOI: 10.1017/s1481803500012690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhaled hypertonic saline on hospital admission rate in children with viral bronchiolitis: a randomized trial

Abstract: Objective: We sought to determine whether inhaled 3% hypertonic saline (HS) reduces admission to hospital in ambulatory children with moderately severe viral bronchiolitis. Secondary objectives compared changes in respiratory scores before and after treatment and assessed the need for unscheduled medical intervention within 7 days. Methods: Children under the age of 2 years presenting with moderately severe viral bronchiolitis to the emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 30 publications
2
37
0
2
Order By: Relevance
“…1 In conclusion, we agree with the AAP guidelines 1 regarding the use of nebulized hypertonic saline to reduce bronchiolitis scores and LOS for infants with bronchiolitis who are expected to be hospitalized for more than 72 hours. We also note that recent trials [21][22][23][24][25][26][27][28][29][30][31] suggest that hypertonic saline reduces admission rates from the ED, and we believe there may be a role for hypertonic saline in this setting. Given the safety of this therapy and the lack of other effective therapies for these patients, use of hypertonic saline should be attempted in multiple doses in all patient care settings where nebulization can be administered.…”
Section: Clinical Trials Evaluating Hypertonic Saline Use In Hospitalsmentioning
confidence: 74%
See 2 more Smart Citations
“…1 In conclusion, we agree with the AAP guidelines 1 regarding the use of nebulized hypertonic saline to reduce bronchiolitis scores and LOS for infants with bronchiolitis who are expected to be hospitalized for more than 72 hours. We also note that recent trials [21][22][23][24][25][26][27][28][29][30][31] suggest that hypertonic saline reduces admission rates from the ED, and we believe there may be a role for hypertonic saline in this setting. Given the safety of this therapy and the lack of other effective therapies for these patients, use of hypertonic saline should be attempted in multiple doses in all patient care settings where nebulization can be administered.…”
Section: Clinical Trials Evaluating Hypertonic Saline Use In Hospitalsmentioning
confidence: 74%
“…Since Zhang's systematic review, 2 additional trials in the ED, with admission rates as a primary outcome, have been published. 27,31 A larger study by Wu et al 31 supported a reduction in hospital admissions of about 50%. Although this reached statistical significance, the number of patients enrolled did not meet the power criteria.…”
Section: Clinical Trials Evaluating Hypertonic Saline Use In Hospitalsmentioning
confidence: 94%
See 1 more Smart Citation
“…7 Since this review, additional studies have evaluated HS in infants with bronchiolitis: 1 in an ambulatory setting, 3 in an emergency department (ED), and 5 in hospitalized patients. 6,[8][9][10][11][12][13][14][15][16] All of these studies have shown a reduction in pulmonary severity scores and/or a trend toward reduced admission rates in the HS group. Of note, all investigations to date have shown HS to be safe, with no patients experiencing decreased oxygen saturation, apnea, or cyanosis after administration of the medication.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10]15,16,21 However, HS appears to be safe when used alone to treat infants with bronchiolitis. 11,12,22 Another limitation is that the modified BSS is not widely used and has not been externally validated. 8 However, it has been an established respiratory assessment tool in our institution for more than 7 years and incorporates all the major criteria used by other scoring systems for bronchiolitis, including oxygen saturation.…”
Section: Articlementioning
confidence: 99%